PENENTUAN KADAR VITAMIN C BEBERAPA JENIS CABAI (Capsicum sp.) DENGAN SPEKTROFOTOMETRI UV-VIS - Lilis Rosmainar Tambunan; Widia Ningsih; Ni Putu Ayu; Haula Nanda (Universitas Airlangga, 2018)
Vitamin C is one of the nutrients that act as antioxidants and effectively overcome free radicals that can damage cells or tissues, including protecting the lens from oxidative damage caused by radiation. Vitamin C is widely found in fruits, and vegetables, one of them in chili. Vitamin C in chili has a function as a good antioxidant for the body (able to increase the immune system absorbed by calcium in the body. This study aims to determine the levels of vitamin C contained in some types of chili using UV-Vis spectrophotometry method and conduct a preliminary test. The highest levels of vitamin C obtained by using spectrophotometric method at 200 nm wavelength were on red curly pepper (50 g/100 g) and followed by chili jablay orange-red (38 g/100 g), green cayenne (29 g/100 g), red pepper large (22 g/100 g), and large green chili (9 g/100 g). While based on preliminary test it was found that all chilies contain saponins, as well as only large red pepper (sample 1) and red curly pepper (sample 4) containing flavonoids Keywords: capsicum, chilly, spectrophotometry